Villancicos, que se han de cantar la noche de Navidad - Pujolar, José (Barcelona : En la imprenta de Rafael Figuero, à los Algodoneros, 1688)
Features Christmas carols, to be sung on Christmas night in the Holy Church of Urgel. This in the year of 1688 and dedicated to the very illustrious canon-prelates. As well as the cabildo of said Holy Church; Joseph Pujolar being the master of the chapel.
Villancicos, que se han de cantar la noche de Navidad en la Santa Iglesiade Urgel, este año de 1688 : dedicados a los muy ilustres señores canonigos prelados, y cabildo de dicha Santa Iglesia / siendo maestro de capilla el licenciado Joseph Pujolar.
Written by José Pujolar and published by Barcelona : En la imprenta de Rafael Figuero, à los Algodoneros in 1688, this book has significant foxing. Made up of 8 unnumbered pages that are verydelicate. Additionally, it is written entirely in Spanish.
Keywords: Rare books, Villancicos, que se han de cantar la noche de Navidad, Spanish, Christmas Carols, Christmas, Christmas Music, Spanish Christmas music, Spain